REFORMASI BIROKRASI DAN KEBIJAKAN PELAYANAN PUBLIK PADA SEKTOR PERIZINAN - Ramadhan, Yoga Surya; Fitria, Fitria (Fakultas Hukum Universitas Jambi, 2021)
The writing of this article is a research using the normative method (doctrinal), which aims to describe how the direction of public service policy reform, especially in regulating the operation of permits in Indonesia. who issued the permit. Policies related to licensing issued by the government are a guide in the implementation of licensing services. Provisions regarding licensing issues are very broad because of the diversity of types of licenses issued according to the position of each agency itself, so over time there will continue to be reforms in public service policies, especially in terms of licensing policies. These reforms are of course aimed at creating the conditions for public services desired by the community, namely licensing services that are easy, fast, and efficient.